Avaliação do percurso dos pacientes e da qualidade do preenchimento dos prontuários nas disciplinas obrigatórias do departamento de Saúde Bucal da Criança e do Adolescente - Lorena Castro Rocha (2022)
The aims of this census-type longitudinal retrospective study were to verify the patients' journey towards preventive and curative dental care clinics provided by the Department of Oral Health for Children and Adolescents (SCA) of the Faculty of Dentistry at the Federal University of Minas Gerais (UFMG). Clinical records evaluated in the present study came from the database of the university extension project called "Health Promotion and Management of the SCA’s Patient Database" which manages the flow of patients in the pediatric dentistry department's clinics. It was considered eligible those dental records related to patients seen in the Pediatric Dentistry clinic, from the second half of 2013 to the second half of 2019. In addition, to be included in the sample dental records had to comprise the informed consent form signed by the person responsible for the patient, be related to patients who had their first clinical appointment in one of the mandatory subjects of the SCA, and had at least one discharge after the first oral health care appointment, having also attended at least one preventive maintenance oral health consultation. All dental records were evaluated by a single researcher, who had been previously calibrated (Kappa intra-examiner: 0,888). The main outcome evaluated was the probability of referring patients to curative dental treatment in the FAO UFMG mandatory subjects. The assessment of patients' journey between preventive/maintenance and curative care was performed through survival analysis, which analyzed the time interval between dental appointments, the type of clinical appointment (whether preventive or curative) and patient's sex and age. The quality of filling in the dental records was descriptively evaluated. The cox analysis results were provided in risk ratio (HR), 95% confidence interval (CI) and significance level p≤ 0.05. This study was approved by the UFMG Research Ethics Committee (CAAE: 44625221.4.0000.5149). Of the 1390 eligible dental records, 296 met the inclusion criteria, 141 (47.6%) referred to female patients and 155 (52.4%) to male patients. The mean age of patients at the first consultation was 5.97 years (SD = 2.305). Of the 296 eligible dental records, none of them were adequately filled in for all the analyzed sections. In order to evaluate the outcome ‘referral to dental treatment’, 972 dental appointments were counted, and in 281 (28.9%) the patients had a need for curative treatment and in 691 (71.1%) the patients had no need for curative treatment. The probability of needing a referral for curative treatment at six months of follow-up was 18.9%, 42.6% at 12 months, and 52,5% at 18 months. There was no difference in the probability of treatment referral in the follow-up time between female and male patients (HR = 1,13; [0,89 – 1,43]; p = 0,304). Patients aged 9 years or younger were 2.07 times more likely to be referred to curative treatment with follow-up time than patients aged 10 years or older (HR = 2,07; [1,62 – 2,64]; p < 0,001). Thus, it was concluded that follow-up intervals of more than six months increased the chance of the patient needing curative treatment, and this probability was higher among children aged 9 years or less. The quality of filling out dental records by undergraduate students is utterly deficient.